2009
DOI: 10.1152/ajprenal.90727.2008
|View full text |Cite
|
Sign up to set email alerts
|

Strain differences in urinary factors that promote calcium oxalate crystal formation in the kidneys of ethylene glycol-treated rats

Abstract: Ethylene glycol (EG)-induced hyperoxaluria is the most commonly employed experimental regimen as an animal model of calcium oxalate (CaOx) stone formation. The variant sensitivity to CaOx among different rat strains has not been fully explored, although the Wistar rat is known to accumulate more CaOx in kidney tissue after low-dose EG exposure than in the Fischer 344 (F344) rats. Supersaturation of CaOx in tubular fluid contributes to the amount of CaOx crystal formation in the kidney. We hypothesized that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 40 publications
(49 reference statements)
1
21
0
Order By: Relevance
“…In this model, the daily fluid consumption, 24-h urine volume, and creatinine excretion (when adjusted by body weight) were not different between strains and were not affected by EG treatment (34). After 2-wk treatment with EG in this model, urinary and plasma oxalate concentrations were markedly increased (5-to 20-fold) in Wistar rats, but were not significantly increased in F344 rats (34).…”
Section: Methodsmentioning
confidence: 70%
See 3 more Smart Citations
“…In this model, the daily fluid consumption, 24-h urine volume, and creatinine excretion (when adjusted by body weight) were not different between strains and were not affected by EG treatment (34). After 2-wk treatment with EG in this model, urinary and plasma oxalate concentrations were markedly increased (5-to 20-fold) in Wistar rats, but were not significantly increased in F344 rats (34).…”
Section: Methodsmentioning
confidence: 70%
“…Previous studies using this treatment regimen showed that the EG treatment did not affect body weight or body weight gain in either rat strain (34). Compared with the age-matched Wistar rats, F344 rats did have lower body weights in both control and treated groups.…”
Section: Methodsmentioning
confidence: 71%
See 2 more Smart Citations
“…Ethylene glycol is metabolised to glycolate and glyoxylate which cause tissue destruction particularly due to COM deposition in the renal tissue. The oxalic acid formed by the metabolism combines with calcium to form calcium oxalate which gets deposited in the kidney leading to renal failure [15].…”
Section: Discussionmentioning
confidence: 99%